2015
DOI: 10.1080/08897077.2015.1010032
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Opioid Overdose Prevention and Naloxone Prescribing: Implications for Translating Community Programming into Clinical Practice

Abstract: Background As physicians have increased opioid prescribing, overdose deaths from pharmaceutical opioids have substantially increased in the United States. Naloxone hydrochloride (naloxone), an opioid antagonist, is the standard of care for treatment of opioid induced respiratory depression. Since 1996, community-based programs have offered overdose prevention education and distributed naloxone for bystander administration to people who use opioids, particularly heroin. There is growing interest in translating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
139
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 92 publications
(157 reference statements)
4
139
0
1
Order By: Relevance
“…The program continues to expand, and had distributed 1,975 naloxone kits and received reports of 335 naloxone administrations as of November 2015. Similar to other reports, 10,12 we found that people at risk of opioid overdose were willing to be trained and to use naloxone to respond …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The program continues to expand, and had distributed 1,975 naloxone kits and received reports of 335 naloxone administrations as of November 2015. Similar to other reports, 10,12 we found that people at risk of opioid overdose were willing to be trained and to use naloxone to respond …”
Section: Discussionsupporting
confidence: 78%
“…[6][7][8][9] The current evidence on the effectiveness of naloxone programs remains limited. [10][11][12][13][14] Naloxone programs are promising for reducing mortality 15 and being cost-effective, 16 and there are several descriptive reports of program data in the literature. 10 To date, no rigorous prospective studies have been completed to assess impact on rates of overdose death.…”
mentioning
confidence: 99%
“…These programs have been effective in the United States and the United Kingdom. [27][28][29][30][31][32] Similar programs exist in Canada and aim to provide education about prevention, recognition and treatment of opioid overdose. Providing take-home naloxone through emergency departments or supervised consumption sites to high-risk individuals is another cost-effective strategy with high acceptance rates.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33] Moreover, take-home naloxone is acceptable to patients receiving opioids for chronic pain, 34,35 with recipients stating that receiving education about the risks of opioids and having naloxone available in the event of overdose would be beneficial and that they would not be offended if offered the product.…”
mentioning
confidence: 99%
“…This intervention has been associated with both a reduction in the likelihood of death when an overdose occurs and a substantial relative reduction in opioid overdose mortality in communities that distribute the medication. [4][5][6] Prescribing naloxone through primary care to patients receiving opioid analgesics, in contrast, has not been well studied. Implementation of a naloxone Bco-prescription^program for patients on long-term opioids at the Fort Bragg U.S. Army base was associated with a decline in opioid overdoses from eight to zero per month.…”
Section: Introductionmentioning
confidence: 99%